2019
DOI: 10.1016/j.pbb.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine conditioning history on alcohol and methamphetamine self-administration in rats

Abstract: Background.-Smoking constitutes a significant public health risk. Alcohol and methamphetamine use disorders are also highly co-morbid with smoking, further increasing negative health outcomes. An important question in determining the underlying neurobiology of nicotine poly-drug use is understanding whether having a positive history with nicotine effects alters later drug-taking behavior. Methods.-The current experiments sought to elucidate whether having an appetitive nicotine conditioning history would affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…5,6,19,43 For adults, clinical and preclinical studies show that female adults are more sensitive to nicotine, than males. 44,45 While studies have shown nicotine conditioning decreases METH self-administration in female rats, 45 we observe nicotine-induced discrimination between reinforced and nonreinforced responding after day 3 of selfadministration and overall METH intake (mg/kg) in female adults. Conversely, low-dose nicotine exposure had no effect on METH selfadministration in male adults.…”
Section: Discussionmentioning
confidence: 60%
“…5,6,19,43 For adults, clinical and preclinical studies show that female adults are more sensitive to nicotine, than males. 44,45 While studies have shown nicotine conditioning decreases METH self-administration in female rats, 45 we observe nicotine-induced discrimination between reinforced and nonreinforced responding after day 3 of selfadministration and overall METH intake (mg/kg) in female adults. Conversely, low-dose nicotine exposure had no effect on METH selfadministration in male adults.…”
Section: Discussionmentioning
confidence: 60%
“…Supporting the latter idea, animal models such as the "discriminated goal-tracking task" show that drug interoceptive stimuli can readily guide reward-seeking behavior [22,[96][97][98][99]. In these studies, the experimenter administers either a drug (e.g., nicotine) or vehicle (e.g., saline) prior to daily conditioning sessions.…”
Section: Animal Modelsmentioning
confidence: 99%